Biogeochemical proxies and diatoms in surface sediments across the Drake Passage reflect oceanic domains and frontal systems in the region. (May 2019) - Cárdenas, Paola; Lange, Carina B.; Vernet, Maria; Esper, Oliver; Srain, Benjamin; Vorrath, Maria-Elena; Ehrhardt, Sophie; Müller, Juliane; Kuhn, Gerhard; Arz, Helge W.; Lembke-Jene, Lester; Lamy, Frank
Highlights: Latitudinal gradient in sediment composition associated with oceanic fronts. Diatom concentrations correlated with biogenic opal. Diatom species distribution reflects N-S environmental gradients. Pigments and sterols in Bransfield Strait associated with high productivity pulses. Low chl a :phae suggests phytoplankton carbon degradation. Sterols assigned to different biological sources. Abstract: The Antarctic Circumpolar Current is the world's largest current system connecting all major ocean basins of the global ocean. Its flow, driven by strong westerly winds, is constricted to its narrowest extent in the Drake Passage, located between South America and the Antarctic Peninsula. Due to the remoteness of the area, harsh weather conditions and strong bottom currents, sediment recovery is difficult and data coverage is still inadequate. Here, we report on the composition of 51 surface sediments collected during the R/V Polarstern PS97 expedition (February–April 2016) across the western and central Drake Passage, from the Chilean/Argentinian continental margin to the South Shetland Islands and the Bransfield Strait (water depth: ∼100–4000 m). We studied microfossils (diatoms), bulk sediment composition and geochemical proxies (biogenic opal, organic carbon, calcium carbonate, carbon and nitrogen stable isotopes, sterols and photosynthetic pigments), and evaluated how they respond to, and reflect oceanic domains and polar to subpolar frontal systems in this region. Our multi-proxy approach shows a strong relationship between the composition of surface sediments and ocean productivity, terrigenous input, intensity of ocean currents, and ice proximity, clearly differentiating among 4 biogeographical zones. The Subantarctic Zone was characterized by warmer-water diatoms, high carbonate (>45%) and low organic carbon contents (avg. 0.26%), as well as low concentrations of pigments (avg. 1.75 μg/g) and sterols (avg. 0.90 μg/g). A general N-S transition from carbonate-rich to opal-rich sediment was observed at Drake Passage sites of the Polar Front and Permanently Open Ocean Zone. These sites were characterized by low organic carbon content (0.22%), high relative abundances of heavily silicified diatoms (≥60% Fragilariopsis kerguelensis ), and abundant foraminifera at shallower stations. Approaching the Antarctic Peninsula in the Transitional Zone, an increase in the concentrations of pigments and sterols (avg. 2.57 μg/g and 1.44 μg/g, respectively) and a strong decrease in carbonate content was observed. The seasonal Sea-Ice Zone in the southern section of the study area, had the highest contents of biogenic opal (avg. 14.6%) and organic carbon (avg. 0.7%), low carbonate contents (avg. 2.4%), with the occurrence of sea-ice-related diatoms and sterols. In all zones, terrigenous input was detected, although carbon/nitrogen ratios and δ 13 Corg suggest a predominance of marine-derived organic matter; lower values of δ 13 Corg occurred south of the Polar Front. The new results presented here constitute a highly valuable reference dataset for the calibration of microfossil and geochemical proxies against observational data and provide a useful regional baseline for future paleo-research.